Reading the silence: Canadian library responses to racial injustice - Matthews, Amber (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2021)
This paper presents the findings of a research study on the formal response of the Canadian library community to the mass Black Lives Matter (BLM) social movement in the wake of George Floyd’s death and the resulting global protests over the summer of 2020. The study employed mixed-method content analysis and its principal goals were to (a) identify formal responses between May to August 2020; (b) analyze themes across how the Canadian library community views and situates itself within conversations of racial justice; and (c) identify the scale and scope of commitments made for future accountability and research. The results show that one third (34%) of the Canadian library community formally responded with an organizational statement and even less situated their organizations as contributors to systemic racism in Canadian society.